2009
DOI: 10.1007/s10620-009-1036-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Clinical Impact of Capsule Endoscopy in Patients with Overt Obscure Gastrointestinal Bleeding

Abstract: Patients with massive and overt OGIB are the best candidates for CE. Earlier CE, virtually within a week, contributes to the better diagnostic yield of the procedure. Careful follow-up seems necessary for patients with massive bleeding even in cases of negative CE findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 41 publications
5
59
2
1
Order By: Relevance
“…Pennazio et al [16] reported that the diagnostic yield of CE was significantly higher in patients with ongoing overt OGIB (92.3%), intermediate in patients with occult OGIB (44.2%) and lowest in patients with previous overt OGIB (12.9%). In the overt OGIB group, the diagnostic yield was inversely proportional to the length of time since the last bleeding episode, as delay in the use of CE allows for healing of the bleeding site [24] . CE thus has its highest diagnostic yield in patients with ongoing and overt bleeding [16,25] .…”
Section: Capsule Endoscopymentioning
confidence: 99%
“…Pennazio et al [16] reported that the diagnostic yield of CE was significantly higher in patients with ongoing overt OGIB (92.3%), intermediate in patients with occult OGIB (44.2%) and lowest in patients with previous overt OGIB (12.9%). In the overt OGIB group, the diagnostic yield was inversely proportional to the length of time since the last bleeding episode, as delay in the use of CE allows for healing of the bleeding site [24] . CE thus has its highest diagnostic yield in patients with ongoing and overt bleeding [16,25] .…”
Section: Capsule Endoscopymentioning
confidence: 99%
“…Most published reports on CE in OGIB are limited to small groups of patients [6][7][8] . Although most differentiate between occult and overt GI bleeding when analyzing diagnostic yield, they do not identify the optimum time for performing CE in the overt GI bleeding group.…”
Section: Introductionmentioning
confidence: 99%
“…Angiodysplasia was the most common finding among patients with positive VCE (70%) and the majority of them received some mode of treatment leading to bleeding resolution (69%). Esaki et al (51) with positive VCE findings. The reported re-bleeding rate (10.7%) was equivalent to those in previous studies (6-10%), implying that use of anti-coagulation therapy or type of therapy may pose a certain effect.…”
Section: Impact On Subsequent Therapeutic Strategies and Clinical Outmentioning
confidence: 96%
“…This might be linked to the increased prevalence of angiodysplasia among older individuals and the high incidence of angiodysplasia when chronic kidney disease is present (2,64). Documented fall in hemoglobin below 8 g/dL as well as higher need of blood units transfusion prior to VCE mandates clinical reevaluation and pursue of further endoscopic investigations (27,28,30,51,52).…”
Section: Predictive Factors For Re-bleeding After Index Vcementioning
confidence: 99%